Transcriptomic and metabolomic analyses reveal the essential nature of Rab1B in Toxoplasma gondii - He, Kai; Wang, Qiangqiang; Gao, Xuwen; Tang, Tao; Ding, Huiyong; Long, Shaojun (Parasites & vectors, 2023)
The protozoan parasite Toxoplasma gondii encodes a dozen Rab proteins, which are parts of the small GTPase superfamily and regulate intracellular membrane trafficking. Our previous study showed that depletion of Rab1B caused severe defects regarding parasite growth and morphological structure, yet early defects of endocytic trafficking and vesicle sorting to the rhoptry in T. gondii are not expected to have a strong effect. To understand this discrepancy, we performed an integrated analysis at the level of transcriptomics and metabolomics. In the study, tetracycline-inducible TATi/Ty-Rab1B parasite line treated with ATc at three different time points (0, 18 and 24 h) was used. We first observed the morphological changes caused by Rab1B depletion via transmission electron technology. Then, high-throughput transcriptome along with non-targeted metabolomics were performed to analyze the RNA expression and metabolite changes in the Rab1B-depleted parasite. The essential nature of Rab1B in the parasite was revealed by the integrated omics approach. Transmission electron micrographs showed a strong disorganization of endo-membranes in the Rab1B-depleted parasites. Our deep analysis of transcriptome and metabolome identified 2181 and 2374 differentially expressed genes (DEGs) and 30 and 83 differentially expressed metabolites (DEMs) at 18 and 24 h of induction in the tetracycline-inducible parasite line, respectively. These DEGs included key genes associated with crucial organelles that contain the rhoptry, microneme, endoplasmic reticulum and Golgi apparatus. The analysis of qRT-PCR verified some of the key DEGs identified by RNA-Seq, supporting that the key vesicular regulator Rab1B was involved in biogenesis of multiple parasite organelles. Functional enrichment analyses revealed pathways related to central carbon metabolisms and lipid metabolisms, such as the TCA cycle, glycerophospholipid metabolism and fatty acid biosynthesis and elongation. Further correlation analysis of the major DEMs and DEGs supported the role of Rab1B in biogenesis of fatty acids (e.g. myrisoleic acid and oleic acid) (R > 0.95 and P < 0.05), which was consistent with the scavenging role in biotin via the endocytic process. Rab1B played an important role in parasite growth and morphology, which was supported by the replication assay and transmission electron microscopy observation. Our multi-omics analyses provided detailed insights into the overall impact on the parasite upon depletion of the protein. These analyses reinforced the role of Rab1B in the endocytic process, which has an impact on fatty acid biogenesis and the TCA cycle. Taken together, these findings contribute to our understanding of a key vesicular regulator, Rab1B, on parasite metabolism and morphological formation in T. gondii.